The Biotechnology industry in Germany and Japan - Christian Müller (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2001)
Biotechnology is considered as one of the key high-technology sectors in the future. It has been increasingly accepted that small, innovative businesses were the major stimulus for the development of this emerging industry. Many studies on new entrepreneurial entrants in biotechnology are mainly addressed to the situation in the United States and neglected developments in other countries. Therefore, the present paper concentrates on two latecomers into the industry of biotechnology, namely Japan and Germany, and addresses the question how different institutional frameworks may have an impact on its emergence. More specifically, we investigate the role of venture capital, governmental initiatives, large companies, and entrepreneurship on the development and current situation of the biotechnology industry. The comparison of the biotechnology industry between two countries against the background of their different institutional settings provides some important insights for management scholars as well as policy makers.
urn:nbn:de:gbv:830-opus-1525
Keywords: 650; Biotechnologische Industrie; Japan; Deutschland